Ex-Engineer For Amazon Is Convicted Of Hacking. - CONGER, KATE (New York Times, 2022)
The article reports on the decision by a Seattle, Washington jury to convict former Amazon engineer Paige Thompson on the charges of wire fraud and hacking due to his alleged theft of CapitalOne customers' personal information.